The Effect of Ewom on Brand Image and Purchase Intention in the Astro E-grocery Application - Prahasti, Gyan; Lewi, Agustina; Bharwani, Kenchen Arjandas (Journal of Digital Marketing and Halal Industry, 2023)
Electronic Word of Mouth (eWOM) can be used as a marketing method by companies in developing strategic brands. eWOM communication may have a strong influence on brand image and purchase intention. The rapid growth of social media provides a positive opportunity for companies to approach consumers through eWOM strategies. One of element that influences a person when shopping for daily necessities online or wholesale/e-grocery is e-wom. This paper aims to develop a conceptual framework that provides practical and theoretical insights into e-grocery consumers' use of social media as a promotional tool for electronic word of mouth (eWOM) and its impact on brand image (BI) and purchase intention (PI). Using a quantitative survey method with 26 questions, the questionnaire was distributed via Google Forms to 158 respondents selected based on followers and owners of Astro e-grocery mobile apps located in the Jakarta area and its surroundings using path analysis techniques in Structural Equation Modeling (SEM). The finding is that E-WOM significantly affects Purchase Interest with Brand Image as an intervening variable. The results of this research can be applied practically to help company marketing departments and advertising agencies present information according to consumer characteristics to influence purchasing intentions. Theoretical implications can also help further research in analyzing the factors influenced by EWOM.